2020
DOI: 10.1016/j.jinf.2020.02.026
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 spike-host cell receptor GRP78 binding site prediction

Abstract: Objectives: Understanding the novel coronavirus (COVID-19) mode of host cell recognition may help to fight the disease and save lives. The spike protein of coronaviruses is the main driving force for host cell recognition. Methods: In this study, the COVID-19 spike binding site to the cell-surface receptor (Glucose Regulated Protein 78 (GRP78)) is predicted using combined molecular modeling docking and structural bioinformatics. The COVID-19 spike protein is modeled using its counterpart, the SARS spike. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
401
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 440 publications
(419 citation statements)
references
References 30 publications
11
401
0
7
Order By: Relevance
“…These numbers are continually increasing each day, and the number of confirmed cases at the time of this writing has now exceeded 258,000, with 11,268 confirmed deaths, mostly in China, Europe, and the Islamic Republic of Iran. On 20 January 2020, the National Health Commission of China confirmed human-to-human transmission of the COVID-J o u r n a l P r e -p r o o f Based on its nucleotide sequences, SARS-CoV-2 is a member of Betacoronaviruses, such as the SARS and MERS HCoVs (Chan et al , 2015, Ibrahim et al , 2020.…”
Section: Introductionmentioning
confidence: 99%
“…These numbers are continually increasing each day, and the number of confirmed cases at the time of this writing has now exceeded 258,000, with 11,268 confirmed deaths, mostly in China, Europe, and the Islamic Republic of Iran. On 20 January 2020, the National Health Commission of China confirmed human-to-human transmission of the COVID-J o u r n a l P r e -p r o o f Based on its nucleotide sequences, SARS-CoV-2 is a member of Betacoronaviruses, such as the SARS and MERS HCoVs (Chan et al , 2015, Ibrahim et al , 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Recent in vitro reports have demonstrated that similar host proteins are involved in facilitating cell entry by SARS-CoV-2, such as ACE2 and TMPRSS2[5, 24] Biophysical and structural evidence strongly support an interaction of ACE2 with SARS-CoV-2 spike protein, similar to SARS-CoV spike protein[12, 13]. Molecular docking studies have also suggested that SARS-CoV-2 spike protein can interact with cell-surface GRP78[25]. Indirect evidence for a role of CD147 in SARS-CoV-2 binding has been demonstrated in vitro with the use of an anti-CD147 intervention that prevented virus replication[26].…”
Section: Introductionmentioning
confidence: 99%
“…Infection can occur from animal to animal and from animal to human in the case of close contact with infected animals (Azhar et al, 2014;Han et al, 2016). Additionally human to human transmission was reported for human coronaviruses (Elfiky, 2020a(Elfiky, , 2020bIbrahim et al, 2020;Yang, 2020). SARS, MERS, and SARS-CoV-2 caused diseases are characterized by a lower respiratory ailment like bronchitis, bronchiolitis, and pneumonia, which leads to death with different ratios (Bogoch et al, 2020;Graham et al, 2013;van den Brand et al, 2015;Wu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%